Potential of the CLARA test facility for VHEE radiotherapy research - Angal-Kalinin, Deepa; Boogert, Stewart; Jones, James Kevin (Frontiers in Physics, 2024)
The Compact Linear Accelerator for Research and Applications (CLARA) is a test facility at the STFC Daresbury Laboratory, which is capable of delivering ultra-bright electron bunches of up to 250 MeV beam energy. A new beam line has been designed to maximise the exploitation of the CLARA facility in a variety of scientific fields, including novel acceleration and new modalities of radiotherapy. In this paper, we present the specification and design of this beam line to explore the possibilities of pursuing R&D in very high-energy electron (VHEE) radiotherapy and VHEE with FLASH radiotherapy. We describe the beam line design, including the flexibility of the beam optics to focus the beam in a range of locations and present results from preliminary start-to-end simulations using Monte Carlo tracking codes. We highlight advantages of this beam line, including rapid access to the shielded experimental hutch and the possibilities for the installation of different experimental setups in two dedicated chambers. The beam line includes focussing magnets, extensive diagnostics, and allows in-air installation within the experimental beam line. The facility will allow an experimental programme towards addressing many outstanding issues related to this new radiotherapy modality. We also describe the available flexibility in beam parameters for both conventional dose rates and those entering into the FLASH regime. The possibility of both living cells and treatment planning studies is anticipated to be conducted at this world-class facility.